College Student Meaning Making and Interest Maintenance During COVID-19: From Course-Based Undergraduate Research Experiences (CUREs) to Science Learning Being Off-Campus and Online - Wang, Cong; Bauer, Melanie; Burmeister, Alita R.; Hanauer, David I.; Graham, Mark J. (Frontiers in Education, 2020)
In response to the outbreak of COVID-19 the national landscape of higher education changed quickly and dramatically to move “online” in the spring semester of 2020. While distressing to both faculty and students, it presents a unique opportunity to explore how students responded to this unexpected and challenging learning situation. In four undergraduate STEM courses that incorporated course-based undergraduate research experiences (CUREs), we had an existing study in progress to track students’ interest development at five time points over the spring 2020 semester. Longitudinal survey data from 41 students in these CURE courses demonstrated that students’ situational interest dropped significantly when their CURE courses unexpectedly shifted from hands-on, discovery-based, and laboratory-based instruction to online instruction. Although we observed a dramatic decline in student interest in general after the CURE courses moved fully online, the decline rates varied across students. Students who were able to make meaningful connections between the learning activities and their personal or career goals were more likely to maintain a higher level of interest in the course. While there are a number of theoretical frameworks which could explain these results, the current study was able to collect COVID-19 semester data and provides early evidence about how students stay engaged in their college science courses when facing unexpected challenges and obstacles to their learning.